بلوچستان میں اسلامی قانون سازی کا ارتقاء:تاریخی وتحقیقی جائزہ: Evolution of Islamic Legislation in Balochistan A Historical and Research Review - Hidayat Ullah; Prof. Dr. Shah Moeen ud Din Hashmi (Al Manhal Research Journal, 2024)
The documents of history testify that Balochistan became a part of the Islamic Empire during the reign of the second Caliph Umar Farooq (RA) and its inhabitants accepted Islamic laws wholeheartedly.The companions of Prophet(PBUH)and their disciples played a prominent role in the implementation of Islamic laws in Balochistan and settled the disputes of the people as Mufti and Qazi.Therefore, the Baloch tribes have created a Baloch code of conduct containing the exact Islamic orders. Mir Ahmad Khan (the ancestor of the present Khawanin Qalat) was the first to formally enforce Islamic laws and establish Sharia courts for the settlement of disputes.Later Khan Azam Mir Nasir Khan was the first Khan of Balochistan who started a new,Islamic government and implemented an islamic constitution in Balochistan. This Baloch Islamic constitution was implemented in the entire country and officials were appointed to implement it. After the fall of Kalat, the British are gradually dominating the Baloch areas with their policies and taking away their autonomy from the Baloch in the name of agreements.There was a time when the declared Islamic laws were abolished and the English laws were implemented.A ray of hope for the renaissance of the Islamic system.Khan Kalat began to appear in the era of Mir Ahmad Yar Khan.He had a strong desire to implement Islamic criminal and civil laws in Balochistan.